ASSESSMENT OF SURROGATE MARKERS FOR CARDIOVASCULAR DISEASE IN FAMILIAL MEDITERRANEAN FEVER-RELATED AMYLOIDOSIS PATIENTS HOMOZYGOUS FOR M694V MUTATION IN MEFV GENE - Sahin, Sezgin; Romano, Micol; Guzel, Ferhat; Piskin, David; Poddighe, Dimitri; Sezer, Siren; Kasapcopur, Ozgur; Appleton, C. Thomas; Yilmaz, Ilker; Demirkaya, Erkan (Life, 2022)
Cardiovascular disease (CVD) remains underestimated in familial Mediterranean feverassociated AA amyloidosis (FMF-AA).We aimed to compare early markers of endothelial dysfunction and atherosclerosis in FMF-AA with a homozygous M694V mutation (Group 1 = 76 patients) in the Mediterranean fever (MEFV) gene and in patients with other genotypes (Group 2 = 93 patients). Measures of increased risk for future CVD events and endothelial dysfunction, including flowmediated dilatation (FMD), pentraxin-3 (PTX3), and carotid intima-media thickness (cIMT), and fibroblast growth factor 23 (FGF23) as a marker of atherosclerotic vascular disease were compared between groups. The frequency of clinical FMF manifestations did not differ between the two groups apart from arthritis (76.3% in Group 1 and 59.1% in Group 2, p < 0.05). FMD was significantly lower in Group 1 when compared with Group 2 (MD [95% CI]: 􀀀0.6 [(􀀀0.89)–(􀀀0.31)]). cIMT, FGF23, and PTX3 levels were higher in Group 1 (cIMT MD [95% CI]: 0.12 [0.08–0.16]; FGF23 MD [95% CI]: 12.8 [5.9–19.6]; PTX3 MD [95% CI]: 13.3 [8.9–17.5]). In patients with FMF-AA, M694V homozygosity is associated with lower FMD values and higher cIMT, FGF23, and PTX3 levels, suggesting increased CVD risk profiles. These data suggest that a genotype–phenotype association exists in terms of endothelial dysfunction and atherosclerosis in patients with FMF-AA.
Keywords: Type of access: Open Access; familial Mediterranean fever; M694V homozygosity; AA amyloidosis; cardiovascular disease; flow-mediated dilatation; carotid artery intima-media thickness